In order to let y=0, the x in the following equations have to be:

1. y=2x-2

x=1

2. y=x+2

x=-2

3. y=(2x-2)(x+2)

y=(2x1-2)(-2+2)

=0x0

Thus, y=0

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

y=(3x-5)(x-4)

y=20

because (-5)(-4)=20

y=x^2-x-2

=(x ?*) (x ?~)

Steps to find the values of “?*” and “?~”

---> The product of ?* and ?~ has to be -2.

- List down all the possibilities (The product of ?* and ?~ values is -2)
- In this case, the sum of ?* and ?~ has to be -1
- Choose the correct possibility

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

If the equation is y=x^2 -6x+8

= (x ?*) (x ?~)

-----> The product of ?* and ?~ has to be 8

------> The sum of ?* and ?~ has to be -6

- List down all the possibilities (The product of ?* and ?~ values is -2)
- In this case, the sum of ?* and ?~ has to be -6
- Choose the correct possibility (so that the product of ?* and ?~ values is -2 & the sum of ?* and ?~ is -6

Ans: -2 & -4

## No comments:

## Post a Comment